PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PNPM MANDIRI PERDESAAN DAN EFEKTIFITASNYA TERHADAP KETAHANAN EKONOMI KELUARGA (Studi Di Kecamatan Kalanganyar, Kabupaten Lebak, Banten) - Sulistiawati _ (Universitas Gadjah Mada, 2013)
This paper explained the community’s role in PNPM Mandiri program related to the family economic resilience. The qualitative and quantitative data showed base on the income approach, PNPM Mandiri program implication was quite effective to enhanced the head of family’ income and not yet effective to fulfilled the family income per capita per day based on the UN standard, and also it had not yet optimal in all villages. The condition created different family economic resilience among the poor village with low family economic resilience and family economic resilience at the non-poor village. Based on the expense approach it showed PNPM Mandiri program had not yet showed similar effectiveness level at every village and not yet created similar family economic resilience in every village.Keywords: Community’s Participation, Village Family, PNPM Mandiri, and Family Economic Resilience.